The plea bargain as a criminal policy instrument: the tension about the fundamental guarantees of the defendant - Aires, Murilo Thomas [UNESP]; Fernandes, Fernando Andrade [UNESP] (Inst Brasileiro Direito Processual Penal-ibraspp, 2017)
The present research intends to analyze the plea bargaining based on its political-criminal foundation, in order to achieve the tension it maintains in relation to certain fundamental guarantees of the defendant, especially the one who signs the agreement. On this occasion, there will be substantially a contraposition between the legal procedure of collaboration and the principles of the adversary, ample defense, presumption of innocence, and non-self-incrimination. The application of the plea bargain proves extremely controversial not only in the common sense, often conveyed by the media, but mainly in the technical perspective, especially in relation to the scientific debate, which reflects the complexity of the proposed theme. For an effective approach to the theme, the work uses the deductive, historical-evolutionary and dialectical methods, being the bibliographical research the technique fundamentally used.
Keywords: Plea bargaining; Criminal Policy; Consensual criminal justice; Fundamental Guarantees; Defendant's plea